The association between diabetes and nocturia: A systematic review and meta-analysis - Fu, Zhiwei; Wang, Fang; Dang, Xing; Zhou, Tao (Frontiers in Public Health, 2022)
Background: Many studies have explored the association between diabetes and nocturia, but it remains unclear. This paper systematically analyses existing evidence of the relationship between diabetes and nocturia, including subgroup analysis based on the number of voids, gender and continent, in the hope of reaching more reliable clinical conclusions relating to diabetes and nocturia. Methods: PubMed, Web of Science and Cochrane Library were searched for identifying studies relating to diabetes and nocturia prior to July 2021. Literature quality evaluation was performed using the Newcastle Ottawa Scale. Random effect meta-analysis was used for pooled odds ratios (OR) and confidence intervals (CI) as a means of evaluating the relationship between diabetes and nocturia. Results: 29 of 781 potentially relevant studies were proven to be eligible. The overall pooled OR demonstrated that diabetes increases the risk of nocturia (OR: 1.49; 95% CI: 1.38, 1.61; P<0.00001). The association was found to be more robust among subjects ≥1 void than ≥2 void (OR: 1.74; 95% CI: 1.41, 2.14; P<0.00001 VS OR: 1.45; 95% CI: 1.33, 1.59; P<0.00001), in males than females (OR: 1.59; 95% CI: 1.41, 1.79; P<0.00001 VS OR: 1.41; 95% CI: 1.20, 1.66; P<0.0001) and in Asia than Europe or North America (OR: 1.54; 95% CI: 1.36, 1.75; P<0.00001 VS OR: 1.43; 95% CI: 1.19, 1.72; P =0.0001 VS OR: 1.45; 95% CI: 1.22, 1.73; P<0.0001). Conclusions: Diabetes has an association with a 1.49-fold higher risk of nocturia. This association is more robust for Asian and male subjects or those at a lower nocturia cut-off.